Enhancing the test and evaluation process: implementing agile development, test automation, and model-based systems engineering concepts - Walker, Joshua T., author; Borky, John, advisor; Bradley, Thomas, advisor; Chong, Edwin, committee member; Ghosh, Sudipto, committee member; Jayasumana, Anura, committee member (Colorado State University. Libraries, 2020)
With the growing complexity of modern systems, traditional testing methods are falling short. Test documentation suites used to verify the software for these types of large, complex systems can become bloated and unclear, leading to extremely long execution times and confusing, unmanageable test procedures. Additionally, the complexity of these systems can prevent the rapid understanding of complicated system concepts and behaviors, which is a necessary part of keeping up with the demands of modern testing efforts. Opportunities for optimization and innovation exist within the Test and Evaluation (T&E) domain, evidenced by the emergence of automated testing frameworks and iterative testing methodologies. Further opportunities lie with the directed expansion and application of related concepts such as Model-Based Systems Engineering (MBSE). This dissertation documents the development and implementation of three methods of enhancing the T&E field when applied to a real-world project. First, the development methodology of the system was transitioned from Waterfall to Agile, providing a more responsive approach when creating new features. Second, the Test Automation Framework (TAF) was developed, enabling the automatic execution of test procedures. Third, a method of test documentation using the Systems Modeling Language (SysML) was created, adopting concepts from MBSE to standardize the planning and analysis of test procedures. This dissertation provides the results of applying the three concepts to the development process of an airborne Electronic Warfare Management System (EWMS), which interfaces with onboard and offboard aircraft systems to receive and process the threat environment, providing the pilot or crew with a response solution for the protection of the aircraft. This system is representative of a traditional, long-term aerospace project that has been constantly upgraded over its lifetime. Over a two-year period, this new process produced a number of qualitative and quantitative results, including improving the quality and organization of the test documentation suite, reducing the minimum time to execute the test procedures, enabling the earlier identification of defects, and increasing the overall quality of the system under test. The application of these concepts generated many lessons learned, which are also provided. Transitioning a project's development methodology, modernizing the test approach, and introducing a new system of test documentation may provide significant benefits to the development of a system, but these types of process changes must be weighed against the needs of the project. This dissertation provides details of the effort to improve the effectiveness of the T&E process on an example project, as a framework for possible implementation on similar systems.
Keywords: model-based systems engineering; systems engineering; test engineering; software engineering; agile development; test automation